Deliberate Trust and Intuitive Faith: A Dual‐Process Model of Reliance*. (15th January 2018) - Stoltz, Dustin S.; Lizardo, Omar
Abstract: Drawing on the dual process framework from social and cognitive psychology, this paper reconciles two distinct conceptualizations of trust prevalent in the literature: "rational" calculative and irrational "affective" or normative. After critically reviewing previous attempts at reconciliation between these distinctions, we argue that the notion of trust as "reliance" is the higher order category of which "deliberate trust" and "intuitive faith" are subtypes. Our revised approach problematizes the conflation of epistemic uncertainty with phenomenological uncertainty while providing sound footing for a key sociological insight: that reliance on the routine social order is both the cognitive default and based on substantial practical evidence. We develop two broad suggestions for future research from these implications: (1) sociological research should examine the role of intuitive faith—as opposed to deliberate trust—in late modern societies, and (2) analysts should challenge the role of deliberate trust as the "modal" form of reliance in contemporary research.